COTTON ROOT VOLUME AND ROOT DRY MATTER AS A FUNCTION OF HIGH SOIL BULK DENSITY AND SOIL WATER STRESS - Duruoha, Charles; Piffer, Cassio Roberto; Silva, Paulo Roberto Arbex (IRRIGA, 2008)
COTTON ROOT VOLUME AND ROOT DRY MATTER AS A FUNCTION OF HIGH SOIL BULK DENSITY AND SOIL WATER STRESS Charles Duruoha1; Cassio Roberto Piffer2; Paulo Roberto Arbex Silva2 1United States Department of Agriculture (USDA-ARS), National Soil Dynamics Laboratory, Auburn, AL, U.S.A,. duruohan@juno.com 2Rural Engineering Departament, School of Agronomic Sciences, São Paulo State University, Botucatu, SP 1 ABSTRACT Soil compaction reduces root growth, affecting the yield, especially in the Southern Coastal Plain of the USA. Simulations of the root restricting layers in greenhouses are necessary to develop mechanisms which alleviate soil compaction problems. The selection of three distinct bulk densities based on the Standard Proctor Test is also an important factor to determine which bulk density restricts root penetration. This experiment was conducted to evaluate cotton (Gossypium hirsutum L.) root volume and root dry matter as a function of soil bulk density and water stress. Three levels of soil density (1.2, 1.4, and 1.6 g cm-3), and two levels of water content (70 and 90% of field capacity) were used. A completely randomized design with four replicates in a 3x2 factorial pattern was used. The results showed that mechanical impedance affected root volume positively with soil bulk density of 1.2 and 1.6 g cm-3, enhancing root growth (P>0.0064). Soil water content reduced root growth as root and shoot growth was higher at 70% field capacity than that at 90% field capacity. Shoot growth was not affected by the increase in soil bulk density and this result suggests that soil bulk density is not a good indicator for measuring mechanical impedance in some soils. KEY WORDS: soil density, water stress, root growth. DURUOHA, C.; PIFFER, C. R.; SILVA, P. R. A. VOLUME E MATÉRIA SECA RADICULAR DE ALGODÃO EM FUNÇÃO DA DENSIDADE DO SOLO ELEVADA E DO ESTRESSE HÍDRICO 2 RESUMO A compactação do solo reduz o crescimento radicular e, conseqüentemente, afeta a produção, especialmente no sudoeste do EUA. Simulações de camadas de restrição de raízes em casa de vegetação são necessárias para desenvolver mecanismos que reduzam problemas de compactação dos solos. A seleção de três diferentes densidades de solo baseadas no ensaio de Proctor é também um fator importante para determinar qual densidade restringe a penetração da raiz. O presente trabalho foi realizado para avaliar o volume e matéria seca radicular em função da densidade do solo e da disponibilidade hídrica em algodão (Gossypium hirsutum L.). Foram utilizados três níveis de densidade do solo (1,2; 1,4 e 1,6 g.cm-3) e dois níveis de teor de água no solo (70 e 90% da capacidade de campo). Os tratamentos foram inteiramente casualizados com quatro repetições em arranjo fatorial (3 x 2). Os resultados mostraram que o impedimento mecânico afetou o volume radicular com densidade do solo de 1,2 a 1,6 g.cm-3, proporcionando aumento do crescimento radicular (P>0,0064). A compactação subsuperficial restringiu a matéria seca radicular com densidade do solo de 1,2 cm.cm-3, aumentando a quantidade de matéria seca radicular na camada compactada (P<0,0291). O teor de água reduziu o crescimento radicular onde, na capacidade de campo de 70 %, houve aumento de raízes e da parte aérea, em relação à capacidade de campo de 90%. O crescimento da parte aérea não foi afetado pela densidade do solo, este resultado sugere que a densidade do solo não é um bom indicador de impedimento mecânico em alguns solos. UNITERMOS: densidade do solo, estresse hídrico, crescimento radicular.